KOGNITIF DAN KADAR GULA DARAH PADA PENDERITA DM TIPE II YANG MENDAPATKAN PROGRAM DIABETES SELF MANAGEMENT EDUCATION (DSME) DI DESA AIRMADIDI - Arlien Jeannete Manoppo (Jurnal Skolastik Keperawatan, 2019)
The Diabetes Self Management Education (DSME) program is an appropriate intervention in controlling diabetes mellitus (DM) and cognitive has a role in the success of the program. The purpose of this study was to analyze the relationship between cognitive and blood sugar levels in patients with type II DM who received DSME. The method used in the study was an analytic observational study with a cohort study design, which involved 27 respondents selected through consecutive sampling. The cognitive mean of patients with type II DM, especially those involved in this study, was 26.04, which meant normal or no interference. The mean blood sugar levels pretest (287.78 mg/dl), posttest (222.78 mg/dl), and the difference between pretest and posttest (65 mg/dl). Pearson correlation test mentioned p=0.137 (p>0.05) so that Ha failed to be accepted, there was no significant relationship between cognitive and blood sugar levels in type II DM patients who received the DSME program. The addition of respondents and the length of time the research needs to be done for further research to get better results involving other factors that can affect cognitive or blood sugar levels. Keywords: Blood sugar levels, cognitive, DSME